The Synthesis of CuO/Polystyrene Nanocomposite Superhydrophobic Layer using The Spin Coating Method - Ratnawulan Ratnawulan; Ahmad Fauzi; Sarimai Sarimai (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
This paper shows the synthesis of CuO/Polystyrene(PS) nanocomposite superhydrophobic layer using the spin coating method. The objective of this study was to determine the effect of calcination temperature on the contact angle, morphology, and energy gap of the CuO/PS nanocomposite thin layer. Preparation of copper powder into copper oxide (CuO) nanoparticles using the method of High Energy 3 Dimensional Milling (HEM-3D) for 20 hours. The calcination temperature variations used were 100◦C , 150◦C, 180◦C, 200◦C, and 300◦C. In this study, sample analysis was performed using X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Ultraviolet-Visible (UV-Vis) Spectrophotometry. The contact angle was determined using the sessile drop method. The findings indicate that the calcination temperature affects the contact angle of the nanocomposite thin films the highest contact angle was obtained at 162◦ at a temperature of 200◦C. The results of SEM analysis obtained that at a temperature of 200◦C, the particle size was 62.91 nm and the particles were evenly distributed in the composite layer. The energy gap at 200◦C is 2.03 eV. We found that CuO/PS synthesized at a temperature of 200◦C was superhydrophobic.